Challenges and Outcomes of Augmentation Rhinoplasty in the Hazara Community of Pakistan: A Cross-Sectional Study - Kamal Uddin Khan, Farzana Abdullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Augmentation rhinoplasty focuses on enhancing and altering the nasal structures to deliver a beautiful result and better nose function. A lot of people worldwide, especially persons of Asian and Middle Eastern origin, choose rhinoplasty to enhance a low nasal bump, a tip that doesn’t protrude enough and a thick layer of soft tissue. A major feature of the Hazara community in northern Pakistan is the distinctive shape of their face and nose such as a broad nasal base, low radix and a flat dorsum. Materials & Methods: A cross-sectional study was conducted under the STROBE guidelines and Hilinski Decleration was conducted from July 2022 to January 2023. In this study, patients of Hazara community who underwent augmentation rhinoplasty with the age range of 18 to 50 years seeking aesthetic beautification were included. Results: Intraoperative challenges were documented, with the most common being thick nasal skin (65%) and a low nasal dorsum (70%). Limited availability of septal cartilage necessitated the use of costal cartilage grafts in 30% of cases as depicted in figure 1 and on appliance of chi-square test it was observed that low nasal dorsum was major intraoperative challenge when compared to others with p-value of 0.0002 followed by thick nasal skin. Conclusion: The unique features of the Hazara community mean that augmentation rhinoplasty can be done successfully with customized surgery. The results of this research indicate that tailoring treatments to match patients’ cultures and anatomy is very important. Keywords: rhinoplasty, Hazra community, nasal ala, beautification.